Blockchain-Based Transformation of Academic Data Management for Enhancing University Governance - Nur Azizah; Muhtarom; Omar Arif Al-Kamari (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2026)
Academic data management at universities often faces challenges related to security, transparency, and efficiency. Conventional systems are still vulnerable to manipulation, data duplication, and slow verification processes. This situation demands technological innovation to strengthen academic data governance comprehensively. This study aims to analyze the application of blockchain technology as a solution to transform academic data management and evaluate its contribution to improving security, transparency, and accountability in university governance. The research approach uses a systematic literature review and a comparative analysis of traditional data management models and blockchain based systems. In addition, empirical validation was conducted through a survey involving 120 respondents consisting of academic stakeholders, including lecturers, administrative staff, and students. Furthermore, a mapping of university governance needs and simulation of relevant blockchain architectures for academic applications were conducted. The results show that blockchain integration can improve academic data integrity through distributed recording and encryption mechanisms. This technology also accelerates the diploma verification process, minimizes the risk of document forgery, and increases the efficiency of data exchange between university units. The application of blockchain in academic data management has the potential to become a strong foundation for more transparent, secure, and efficient university governance. This transformation can drive improvements in academic services and support more accurate decision-making based on reliable data.